AB0238 Effects of endothelin A/B receptor antagonist (bosentan) on alpha-smooth muscle actin (α-SMA) and extracellular matrix protein synthesis in primary cultures of systemic sclerosis skin fibroblasts. (23rd January 2014) - Soldano, S.; Montagna, P.; Brizzolara, R.; Ferrone, C.; Parodi, A.; Sulli, A.; Villaggio, B.; Cutolo, M.
Abstract : Background: In systemic sclerosis (SSc) myofibroblasts are cellular mediator of fibrosis by the overproduction of extracellular matrix (ECM) proteins such as collagens and fibronectin (FN) (1, 2). Myofibroblasts, as activated fibroblasts (Fbs), are characterized by the expression of the high contractile protein α-smooth muscle actin (α-SMA), which contributes to give the profibrotic properties of these cells (3, 4). In SSc endothelin-1 (ET-1) plays a key role in the biology of myofibroblasts and its effects are mediated through the ETA and ETB receptors (5-6). Objectives: To investigate the effects of the ETA/B receptor antagonist (ETA/B RA, bosentan) on ET-1-mediated increase of α-SMA expression and COL-1 and FN synthesis in primary cultures of human SSc skin Fbs. Methods: Human Fbs were obtained from skin biopsies of 6 female SSc patients (mean age 65±6 yrs) during diagnostic procedures (Dermatological Clinic) and after informed consent. Local Ethical Committee approved the study. Cultured Fbs at 4th passage were treated with ET-1 (100nM) for 24 and 48 hrs in presence and in absence of ETA/B RA (10mM) pre-treatment (1 hr) in RPMI at 10% of fetal bovine serum, 1% penicillin-streptomycin. Untreated SSc Fbs were used as controls. Primary antibody to human α-SMA (dilution 1:100) was used to evaluate the myofibroblast activity by immunofluorescence (IF). The ECM protein synthesis was investigated by immunocytochemistry (ICC) and western blotting (WB) with relative image and densitometric analysis using primary antibodies to human COL-1 and FN (dilution 1:100). The experiments were done in triplicate and statistical analysis was carried out by non-parametric Friedman test. Results: ET-1 induced an increase in α-SMA protein expression at both 24 and 48 hrs of treatment in primary cultures of SSc skin Fbs vs. untreated cells, as observed by IF. Moreover, the ICC showed that ET-1-treated cells significantly increased COL-1 and FN synthesis at both 24 and 48 hrs (p<0.001 for every protein) vs. untreated Fbs. The data were confermed by WB. Interestingly, ETA/B RA antagonized the ET-1-mediated increase in α-SMA protein expression, as showed by IF, and it determined a statistical significant decrease in COL-1 (p<0.01; p<0.05) and FN (p<0.001;p<0.01) synthesis vs. ET-1-treated SSc Fbs at both 24 and 48 hrs of treatment, as observed by ICC and WB. Conclusions: Results in cultures of SSc Fbs seem to support the possible involvement of ET-1 in increasing the myofibroblast phenotype and its profibrotic role. The ETA/B R antagonism might exert important effects in contrasting the activation of myofibroblasts and their ECM proteins overproduction in SSc. References: Wei J. et al Autoimmun Rev. 2010;10:267-75. Hinz B. J Biochem 2010;43:146-55. Postlethwaite AE. Et al. Curr Opin Rheumatol.2004;16:733-38. Wynn TA. J Pathol 2008;214:199-210. Leask A. Cell Signal.2008;20:1409-14. Lagares D et al. Arthrit Rheum.2010;62:878-88. Disclosure of Interest: None Declared